Lithuanian Riddles of the Pot as Allegories of the Human Life - Kensminienė, Aelita (Tautosakos darbai, 2021)
Further analyzing the rather widespread international phenomenon – the so-called series of suffering in the riddles – this article focuses on the Lithuanian riddles of the pot, namely: ‘When I was young, I used to sit in a golden chair, when I grew old, even the dog does not eat my bones’ and ‘I was made like Adam from clay and annealed in the furnace like the three young people in Babylon. I was sold like Joseph to Egypt by his brothers. I drive a fiery chariot like Elijah. From my insides, the whole family eats, but when I die, they throw my bones over the fence (do not bury them).’ The analysis is based on all the variants of these riddles (both the published and the manuscript ones), their international parallels, and texts belonging to other genres. Despite the common answer to these riddles – pot – and its typical semantic field based on reality, the artistic expressions of these two riddles have little in common: they significantly differ in terms of structure, wording, and semantic. Thus, their recordings are reasonably attributed to different types in the current card file catalogue. The two riddles only share the common motive of bones at the end, which however has different context of the artistic expression and slightly different meaning. Except for some isolated cases and contaminations, the motives like dog does not eat my bones and they throw my bones over the fence (do not bury them) can be discerned only in these two riddle types respectively. The motive dog does not eat my bones is encountered in almost all the available variants of the first riddle and has the meaning of ‘being useless, idle’. However, the motives they throw the bones over the fence or do not bury them, found in the second riddle, also semantically include the aspect of disrespectful treatment of the deceased and neglecting of the proper funeral rites. Perhaps the main objective of this motive is prompting the listener towards the right answer and suggesting that the answer in question is not a human being. The first riddle seems to be of the Baltic origin, as it includes the typically Baltic motive of the golden chair and the common Baltic-Slavic expression dog does not eat (my) bones. Similar motives are encountered in the wedding songs, where they probably suggest the corresponding semantic field, which is narrowed by the pot as an answer to mean blossoming and withering of fertility. This classical riddle is likely to speak of the human life in general, albeit reducing it to the phases of valued youth and useless senility.The significantly more widespread version of the second riddle in Lithuania includes Biblical motives and has most probably found its way from the East, where it had been “Christianized” by a person well versed in the Old Testament and perhaps belonging to the Byzantine culture. Some variants of this riddle do not include Christian motives; such variants are few in Lithuania but abundant among the Eastern Slavs. Although such versions without Christian motives may be of common origins, however, the proportions of the materials suggest higher probability of the Slavic origin of this riddle. Attributing of these riddles to the series of suffering is also somewhat ambivalent: while the first riddle emphasizes the spiritual suffering, the totality of the variants of the second riddle may be rightfully summarized as the description of the pot’s life; descriptions of the suffering being more frequent in the riddles including the Christian motives. Both riddles tacitly compare the clay pot to the man, allegorically describing the shifts occurring in the human life, the inevitability of change and the instability of status. While reminding the perspective of eternity and the direction of the human life towards death, they allegedly fulfil the function of Memento mori and engage in a visual discussion with the Biblical phrase “from dust to dust”.
Keywords: riddles; pot; clay; bones; pottery; Biblical motives; suffering